Collecting all data continuously in wireless sensor networks with a mobile base station. (2015) - Li, Jie; Ye, Xiucai; Xu, Li; Liu, Huaibei
In this paper, we present a novel coding scheme called separate coding (SC) for collecting all data continuously in wireless sensor networks with a mobile base station (mBS). By separately encoding a certain number of data segments in a combined segment, and storing the combined segments in the corresponding buffers of each sensor node, the SC scheme provides an efficient storage method to collect all data segments. By randomly querying a small subset of sensor nodes, the mBS can reconstruct all the original data segments with high probability. We prove that the success ratio of SC-based data collection is very close to 100%. The number of sensor nodes that should be queried by the mBS can be reduced with a few additional storage space in each sensor node. The performance evaluation has been conducted through computer simulations. It further demonstrates the feasibility and superiority of the proposed SC scheme.